Identification and characterization of bile microbiota in patients with biliary obstructive diseases using next-generation sequencing of 16S rRNA and ITS - Wang, Jie; Wang, Yu; Cao, Jin; Chen, Yong; Yu, Juan; Sun, Ning (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundComparative studies of the bile microbiota in different biliary obstructive infections remain limited. This study aims to characterize bile microbiota and investigate differences in microbial profiles across various biliary obstructive diseases.MethodsThis study included patients with biliary obstructive diseases admitted to Jinling Hospital and Suqian First Hospital. The cohort consisted of individuals with benign biliary disorders, malignant biliary obstruction, and biliary obstruction secondary to severe acute pancreatitis (SAP) or intestinal fistulas. A total of 133 bile samples were collected from 118 patients and analyzed using next-generation sequencing (NGS) targeting the bacterial 16S rRNA gene and the fungal internal transcribed spacer (ITS) gene. Clinical data, including routine culture results, were extracted from electronic medical records.ResultsNGS targeting the 16S rRNA and ITS revealed a positive rate of 68.42% for bile samples, which was higher than the culture positivity rate of 60.15%, indicating a significant difference (Chi-square test, p < 0.05). The predominant bacteria identified in the bile samples through NGS were Klebsiella pneumoniae, Acinetobacter baumannii, and Escherichia coli. Bacterial species varied among benign biliary diseases, malignant obstructive diseases, and biliary obstruction caused by SAP or intestinal fistulas. Fungi were detected in 7.52% (10/133) of the samples, with 4 samples obtained from patients with biliary obstructive diseases due to SAP. Microbial diversity and clustering analysis showed no significant differences among various biliary disorders. Based on the culture results, the sensitivity and specificity of NGS were 81.82% and 69.64%, respectively.ConclusionThe composition of bile microbes may be related to the etiology of biliary obstruction. Klebsiella pneumoniae, Acinetobacter baumannii, and Escherichia coli are the predominant bacteria found in bile. NGS can be effectively applied for the identification and characterization of bile microbes associated with various biliary obstruction diseases.